Centrifuge Tests of Macroscopic and Mesoscopic Investigation into Effects of Seismic Histories on Sand Liquefaction Resistance. Issue 8 (11th June 2022) - Ye, Bin; Xie, Xiaoli; Zhao, Teng; Song, Sicong; Ma, Zijun; Feng, Xiaoqing; Zou, Jinhang; Wang, Huihao
ABSTRACT: Centrifuge shaking table tests were conducted to reveal the intrinsic mechanisms of the effects caused by complicated seismic histories on the liquefaction resistance of a saturated sand deposit. The centrifuge model was shaken by a well-designed seismic sequence including 16 shakings in a certain order. Macroscopic and mesoscopic dynamic responses of the sand deposit were measured and analyzed. Experimental results demonstrated that seismic histories had positive or negative effects on sand liquefaction resistance though sand was densified after previous shakings; these effects were well indicated by the changes in anisotropy characteristics of sand fabric caused by the previous shakings.